Self-Development Lecturer Motivation from Support Working System and Work Evaluation - Arfan, Rahmat; Akbar, Indra; Ariansyah, Ricky (PT FORMOSA CENDEKIA GLOBAL, 2024)
Motivating staff at the professional level requires different patterns and styles. Supporting systems offered need to pay attention to support their career development so that automation performance endorses the formation of a lecturer's career. The research method carried out in this paper is a qualitative research method. The target respondents are lecturers at the Kutaraja Banda Aceh Polytechnic with Good Accreditation, with a total of 12 respondents.From the results of this article, the respondents provided quite supportive statements about the campus having provided a supporting system to support lecturers' self-development motivation by establishing institutions. Furthermore, the work evaluation results dominated the conclusion of the interview results, with the process being carried out following the lecturer's obligations. Some lecturers felt that the evaluation had not been carried out maximally.